2017
DOI: 10.3171/2016.2.jns151592
|View full text |Cite
|
Sign up to set email alerts
|

Words are not enough: nonword repetition as an indicator of arcuate fasciculus integrity during brain tumor resection

Abstract: OBJECTIVE Subcortical electrical stimulation during brain surgery may allow localization of functionally crucial white matter fibers and thus tailoring of the tumor resection according to its functional limits. The arcuate fasciculus (AF) is a white matter bundle connecting frontal, temporal, and parietal cortical areas that is often disrupted by left brain lesions. It plays a critical role in several cognitive functions related to phonological processing, but current intraoperative monitoring methods do not y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 51 publications
5
41
1
Order By: Relevance
“…The AF, also known as the dorsal pathway in the dual-stream model of Hickok and Poeppel, 13 is associated with mapping sound to articulatory-based representations (e.g., phonology), which explains the functional association between microstructural changes and phonological deficits observed here. Our findings also support recent results from Sierpowska et al, 29 who reported that monitoring (non)word repetition is relevant near the AF during electro(sub)cortical stimulation for the preservation of language production and, in particular, phonological performance. 25,29 Deficits in language repetition in combination with relatively intact comprehension, as observed in our patient group, are "classically" known in the stroke literature as conduction aphasia.…”
Section: Af and Language Deficitssupporting
confidence: 92%
See 1 more Smart Citation
“…The AF, also known as the dorsal pathway in the dual-stream model of Hickok and Poeppel, 13 is associated with mapping sound to articulatory-based representations (e.g., phonology), which explains the functional association between microstructural changes and phonological deficits observed here. Our findings also support recent results from Sierpowska et al, 29 who reported that monitoring (non)word repetition is relevant near the AF during electro(sub)cortical stimulation for the preservation of language production and, in particular, phonological performance. 25,29 Deficits in language repetition in combination with relatively intact comprehension, as observed in our patient group, are "classically" known in the stroke literature as conduction aphasia.…”
Section: Af and Language Deficitssupporting
confidence: 92%
“…Our findings also support recent results from Sierpowska et al, 29 who reported that monitoring (non)word repetition is relevant near the AF during electro(sub)cortical stimulation for the preservation of language production and, in particular, phonological performance. 25,29 Deficits in language repetition in combination with relatively intact comprehension, as observed in our patient group, are "classically" known in the stroke literature as conduction aphasia. Several studies in patients with a different etiology found a link between this specific aphasia type and damage to the AF (e.g., tumor infiltration, WM tract compression).…”
Section: Af and Language Deficitssupporting
confidence: 92%
“…In fact, previous MEG source-imaging studies reported that during both verbal 55 and non-verbal 34 , 52 , 56 tasks, brain activity in pST and IP regions as well as in Broca’s area was modulated as a function of working memory load. This perspective is also in line with clinical observations showing that patients with lesions encompassing the left AF often demonstrate impaired working memory functions 57 60 and that intraoperative stimulation in awake brain tumor patients in the vicinity of the AF disrupts non-word repetition 61 . Furthermore, the dorsal stream has previously been shown to contribute to complex sequencing in the verbal domain 62 .…”
Section: Introductionsupporting
confidence: 85%
“…The arcuate fasciculus (AF) comprises three pathways: (i) a long direct segment connecting the temporal lobe to the frontal lobe, (ii) an anterior indirect segment connecting the frontal lobe and the inferior parietal lobule (IPL), and (iii) a posterior indirect segment connecting the temporal lobe and the IPL (Catani et al, 2005). To dissect these three AF segments, we used a three-ROI approach (Catani et al, 2005;Glasser and Rilling, 2008;Vaquero et al, 2016;Francois et al, 2016;Sierpowska et al, 2017), where the first ROI was drawn on a coronal plane to capture all the fibers running in the anteriorposterior direction using a DTI FA color map, the second ROI on an axial plane near temporo-parietal junction to capture fibers running to the temporal lobe, and the third ROI on a sagittal plane to capture fibers connecting to the IPL.…”
Section: Deterministic Tractographymentioning
confidence: 99%